2007
DOI: 10.2193/2005-481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Precommercial Thinning on Snowshoe Hares in Maine

Abstract: Snowshoe hares (Lepus americanus) are an important prey species and a dominant herbivore across much of their North American range, and researchers have questioned the influences of forestry practices that alter habitat for hares and the potential community‐level effects on carnivores. We examined the effects of precommercial thinning (PCT) from 1 to 11 years posttreatment on snowshoe hares. In the commercial forests of northern Maine, USA, we counted and cleared hare pellets twice a year during 2001 and 2002 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 40 publications
0
34
2
Order By: Relevance
“…Although densities of adult female deer mice were similar between thinned (averaged 2.3/trapping grid) and unthinned conifer (averaged 1.7/trapping grid) stands, a companion study on the same 37 forest stands examined in this study reported a greater proportion of adult female deer mice were lactating in unthinned stands compared to similar PCT-treated stands (Homyack, 2003). Reproductive output of deer mice may have been affected by treatment; deer mice often have aggressive intra-specific interactions (Martell, 1983b), which may lead to subordinate, non-reproductive individuals occupying areas with lower habitat quality (Van Horne, 1983).…”
Section: Deer Micecontrasting
confidence: 48%
See 3 more Smart Citations
“…Although densities of adult female deer mice were similar between thinned (averaged 2.3/trapping grid) and unthinned conifer (averaged 1.7/trapping grid) stands, a companion study on the same 37 forest stands examined in this study reported a greater proportion of adult female deer mice were lactating in unthinned stands compared to similar PCT-treated stands (Homyack, 2003). Reproductive output of deer mice may have been affected by treatment; deer mice often have aggressive intra-specific interactions (Martell, 1983b), which may lead to subordinate, non-reproductive individuals occupying areas with lower habitat quality (Van Horne, 1983).…”
Section: Deer Micecontrasting
confidence: 48%
“…We recorded species, sex and age (adult or juvenile) of each individual (Homyack, 2003). Traps were checked from 0600 to 1300 h, and after processing, animals were released at the trap site.…”
Section: Small Mammal Trappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, under-representation and misclassification of regenerating stands could significantly affect the reliability of habitat assessments for species that depend on regenerating forest, such as Canada lynx (Lynx canadensis). Snowshoe hares (Lepus americanus) are the primary prey for lynx (O'Donoghue et al, 1997) and high snowshoe hare densities in Maine are associated with coniferregenerating clearcuts (Homyack et al, 2007;Fuller et al, 2007;Hoving et al, 2004). The GAP update methodology provides both the forest regeneration cover type and stand age information (time since harvest) required for applications such as spatially-explicit wildlife habitat modeling.…”
Section: Discussionmentioning
confidence: 99%